Stealth Navigation with iFuse-TORQ Implant for Sacroiliac Joint Fusion Technique Guide - Jia Bao Lin; Bryan L Demyan; Logan M Bushnell; Morgan T Turnow; Benjamin C Taylor (Journal of Orthopaedic Case Reports)
Introduction: Dysfunction of the sacroiliac (SI) joint exists in nearly one-third of patients with lower back pain. There are nuances in diagnosing SI joint dysfunction with a combination of physical exam maneuvers and intra-articular injections. The management of patients with SI joint pain can include posterior pelvic fixation, which traditionally has been described using fluoroscopy to obtain safe placement of implants. Case Report: In this technique guide, we would like to introduce a novel technique of using Stealth navigation to facilitate SI fusion with the iFuse-TORQ implant. Conclusion: SI dysfunction is a common cause of low back pain that can be difficult to diagnose and treat. In this technique guide, we describe the successful treatment of SI pathology using the Stealth Navigation with the iFuse-TORQ implant.